Machining-Induced Burr Suppression in Edge Trimming of Carbon Fibre-Reinforced Polymer (CFRP) Composites by Tool Tilting - Tamás Sándor Tima; Norbert Geier (Journal of Manufacturing and Materials Processing)
Several challenges arise during edge trimming of carbon fibre-reinforced polymer (CFRP) composites, such as the formation of machining-induced burrs and delamination. In a recent development, appropriate-quality geometric features in CFRPs can be machined using special cutting tools and optimised machining parameters. However, these suitable technologies quickly become inappropriate due to the accelerated tool wear. Therefore, the main aim of our research was to find a novel solution for maintaining the machined edge quality even if the tool condition changed significantly. We developed a novel mechanical edge-trimming technology inspired by wobble milling, i.e., the composite plate compression is governed by the proper tool tilting. The effectiveness of the novel technology was tested through mechanical machining experiments and compared with that of conventional edge-trimming technology. Furthermore, the influences of the tool tilting angle and the permanent chamfer size on the burr characteristics were also investigated. A one-fluted solid carbide end mill with a helix angle of 0° was applied for the experiments. The machined edges were examined trough stereomicroscopy and scanning electron microscopy. The images were evaluated through digital image processing. Our results show that multi-axis edge-trimming technology produces less extensive machining-induced burrs than conventional edge trimming by an average of 50%. Furthermore, we found that the tool tilting angle has a significant impact on burr size, while permanent chamfer does not influence it. These findings suggest that multi-axis edge trimming offers a strong alternative to conventional methods, especially when using end-of-life cutting tools, and highlight the importance of selecting the optimal tool tilting angle to minimize machining-induced burrs.